ANALISIS PERFORMA MIXER MIDAS M32 UNTUK STUDIO RECORDING: DI PREGINA ART & SHOWBIZ - Sitepu, Solideo Tanmamana; Ardini, Ni Wayan; Irawan, Ricky (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
Audio mixer have an important role in the operation of an audio sound system to process it in such a way and obtain the desired results. One type of audio mixer that is often used in the modern music industry is a digital mixer, namely the MIDAS type M32 mixer. This research aims to analyze the performance of the MIDAS mixer in the recording studio at Pregina Art Showbiz. The type of research data is qualitative data used to determine the performance of the MIDAS M32 mixer at Pregina Art & Showbiz Bali regarding the channels used in the MIDAS M32 mixer, types of input and output, sound quality, ease of use, size and portability of the MIDAS M32 mixer in recording studios. at Pregina Art Showbiz.The research results show that the performance of the MIDAS M32 mixer in recording studios has high sound quality and advanced features that meet the needs of professionals in the audio industry. MIDAS M32 provides high flexibility for studio recording needs. Sound quality analysis highlights the advantages of the microphone preamp, ADC conversion, and digital signal processing (DSP) system in creating recordings that are sharp, clear, and accurate while having the size and portability to be transported with relative ease thanks to the rugged design. MIDAS M32 is a comprehensive solution for studio recording needs that combines superior sound quality, advanced features, and ease of use at Pregina Art & Showbiz.